The unconsoled - Ishiguro, Kazuo 1954- (Vintage International, 1996)
A surrealistic novel on a man who finds himself in a strange city, not knowing what he is doing there, but everyone seems to know him. What is more, he must be important because people ask him for favors. As he goes from encounter to encounter, the man discovers himself. By the author of The Remains of the Day.